Pengaruh Patch Ekstrak Buah Delima Merah Terhadap Percepatan Penyembuhan Traumatik Ulser pada Tikus Wistar - Maheswari, Gardenisti Putri; Hernawati, Sri; Lestari, Pujiana Endah (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2024)
Traumatic ulcer is one of the disorders of the oral cavity that can be caused by mechanical, thermal, and chemical. Patch one of traumatic ulcer treatment choice are being developed, but the available patch is uneconomic and have side effects. Therefore, the use of natural ingredients is an alternative treatment, such as pomegranate. Pomegranate is known to contain bioactive elements, that can act as anti-inflammatory and antioxidant, that it can accelerate the healing of traumatic ulcers. The aim of this research is to determine the effect of the pomegranate extract patch on the acceleration of ulcer healing. Sample in this research were 25 traumatic ulcered wistar rats which were divided into 5 groups. All groups were condensed the pomegranate extract patch with a concentration of 12.5%; 25%; 50%, positive control (taisho patch), and negative control (placebo). The red pomegranate extract patch can accelerate the healing of traumatic ulcers. There was a significant difference in healing time between all groups (p<0.05), except between the positive control group with a concentration of 50%. pomegranate extract patch affected the acceleration of ulcer healing, with a concentration of 50% pomegranate extract patch was the fastest.